2016
DOI: 10.3892/mco.2016.786
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and early outcome of high-dose-rate Ir-192 brachytherapy as monotherapy in two fractions within 1 day for high-/very high-risk prostate cancer

Abstract: Abstract. The aim of the present study was to evaluate the feasibility and preliminary outcomes of high-dose-rate (HDR)-brachytherapy as a monotherapy in two fractions within 1 day for localized prostate cancer, including high-/very high-risk cases. Among the 68 patients treated with HDR monotherapy between July 2011 and December 2014, 65 had a minimal follow-up of 12 months without adjuvant androgen deprivation therapy and were enrolled in the present study [42/65 (64.6%) exhibited high-/very high-risk diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…To correlate the studies of SBRT in HR patients, we selected 5 studies that reported treating HR patients with HDR monotherapy [47][48][49][50][51] and 14 studies that reported treating HR patients with an HDR BT boost [52][53][54][55][56][57][58][59][60][61][62][63][64][65] ; for this analysis, SBRT mixed and SBRT boost studies were grouped. Tables 3 and 4 summarize the characteristics of the HDR studies included.…”
Section: Correlation With Selected Hdr Seriesmentioning
confidence: 99%
“…To correlate the studies of SBRT in HR patients, we selected 5 studies that reported treating HR patients with HDR monotherapy [47][48][49][50][51] and 14 studies that reported treating HR patients with an HDR BT boost [52][53][54][55][56][57][58][59][60][61][62][63][64][65] ; for this analysis, SBRT mixed and SBRT boost studies were grouped. Tables 3 and 4 summarize the characteristics of the HDR studies included.…”
Section: Correlation With Selected Hdr Seriesmentioning
confidence: 99%
“…For example, the fractionation schedule used in HDR prostate monotherapy have varied from 9 fractions to even 1 fraction (with corresponding doseper-fraction variation from 6 to 20.5 Gy), [11][12][13] with a trend of moving toward extreme hypofractionation. 14,15 HDR brachytherapy for accelerated partial breast irradiation (APBI) of the lumpectomy margin in breast cancer uses a 192 Ir source and delivers dose twice daily, in 10, 8, 7, or 4 fractions with corresponding dose per fraction of 3.4, 4, 5.2, or 7 Gy, respectively, 16 or in 3 daily fractions of 7 Gy/fraction, 17 while singleapplication LDR (or pulsed-dose rate (PDR)) delivers dose of 45 Gy (or 50 Gy) in 3.5−5 d. 16 Eye plaque brachytherapy for ocular tumors uses temporary implementation of low-energy sources (e.g., 125 I or 103 Pd) and delivers a prescribed dose (∼85 Gy in homogeneous dose calculation) with dose rates between 0.4 and 1 Gy/h. 18 In addition, many brachytherapy applications, such as cervical and prostate brachytherapy, are often used in combination with EBRT, which introduce additional temporal variations over the entire treatment course.…”
Section: Spatial-temporal Dose Delivery Characteristics Of Brachytherapymentioning
confidence: 99%
“…In addition, the use of EQD2 in the form of Equation (14) or (15) does not include the effects of overall treatment time for the reference 2 Gy/fraction delivery. The potential effects of variations in the overall treatment times are not considered in this definition of EQD2.…”
Section: Assumptions and Known Limitationsmentioning
confidence: 99%
“…The ability to optimize source dwell positions and dwell times among the inserted needles can result in superior healthy tissue sparing, target coverage, and potentially allow sub‐volume boosting of intraprostatic lesions, which has been hypothesized to further improve local control rates 3,4 . HDR prostate treatments have shown excellent 5‐year biochemical disease‐free survival when delivered in two to three fractions 5‐8 . The quality and effectiveness of the HDR technique is likely associated with the precise capability to deliver the treatment plan.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 HDR prostate treatments have shown excellent 5‐year biochemical disease‐free survival when delivered in two to three fractions. 5 , 6 , 7 , 8 The quality and effectiveness of the HDR technique is likely associated with the precise capability to deliver the treatment plan.…”
Section: Introductionmentioning
confidence: 99%